Heterogeneous Risk Preferences and the Welfare Cost of Business Cycles - Sam Schulhofer-Wohl (Princeton University, Woodrow Wilson School of Public and International Affairs, 2007)
I study the welfare cost of business cycles in a complete-markets economy where some people are more risk averse than others. Relatively more risk-averse people buy insurance against aggregate risk, and relatively less risk-averse people sell insurance. These trades reduce the welfare cost of business cycles for everyone. Indeed, the least risk-averse people benefit from business cycles. Moreover, even infinitely risk-averse people suffer only finite and, in my empirical estimates, very small welfare losses. In other words, when there are complete insurance markets, aggregate uctuations in consumption are essentially irrelevant not just for the average person- the surprising finding of Lucas (1987)- but for everyone in the economy, no matter how risk averse they are. If business cycles matter, it is because they affect productivity or interact with uninsured idiosyncratic risk, not because aggregate risk per se reduces welfare.
Keywords: E32; E21; 330; business cycles; risk aversion; risk sharing; heterogeneity; Konjunktur; Soziale Kosten; Risikoaversion; Versicherung; Produktivität; Theorie